Documentation of Intangible Cultural Heritage (ICH): Mak Yong performing art collection / Mazlina Pati Khan, Andika Abdul Aziz and Khairul Azhar Mat Daud. - Khan, Mazlina Pati; Abdul Aziz, Andika; Mat Daud, Khairul Azhar (Universiti Teknologi MARA Cawangan Selangor, 2018)
United Nations Educational, Scientific, and Cultural Organization (UNESCO) has recognized Mak Yong’s Theater Performing Art as a Masterpiece of Oral and Intangible Cultural Heritage (ICH) of Humanity since September 2005. Unfortunately, Mak Yong was declared as an irrelevant form of performing art due to the prohibition in the year 1991 since the Islamic Party of Malaysia (PAS) took control of the state and views it as being non-compliant to Islamic teachings. To consolidate and nurture appreciation for the culture and heritage within a society, various efforts have been undertaken to protect it by collecting and documenting cultural heritage especially in the manifestation of intangible cultural value. Thus, this study explores the documentation strategy approach obtainable in cultural heritage institutions on preserving and safeguarding ICH collections. A pure qualitative methodological approach was used by employing a case study design, semi-structured interviews were conducted to examine the aperture on the implementation of documenting ICH collection in the National Archives, National Museum, and the National Library of Malaysia.